A socio-economic study of East London, Cape Province, with special reference to the non-European peoples - Bettison, D G (Rhodes University, Faculty of Humanities, Department of Sociology, 1951)
From Forward: The development of gold mines in the Orange Free State is likely to be to modern East London what Kaffir Wars were to old East London. "The Fighting Port", as it is commonly called, is the nearest harbour to these mines and is linked by good rail, road and air facilities. A wide variety of industry is already established. Development is likely to be rapid. At present the City contains over 80,000 persons, and with the addition of peri-urban suburbs has doubled its population in just over fifteen years. In the past is has claimed to be the healthiest holiday resort in the Union. This year a City-wide campaign has been organised to fight tuberculosis, as the City's statistics indicate that it has one of the highest rates of anywhere in the world. Within twelve years two government sided commissions of enquiry have sat in the City and reported on the administration and living conditions of the city's African populaton. Extremely strong adjectives have been used to describe, and drastic recommendations made to improve the socio-economic and general conditions of the African people. Under the holiday atmosphere of the City lies a very serious, complex, and potentially dangerous human problem.
Keywords: East London (South Africa) -- Social conditions; East London (South Africa) -- Economic conditions; Rural-urban migration -- South Africa